الصورة النمطية للإسلام والمسلمين في الإعلام الأمريكي والمتغيرات الراهنة - رزيوق، شريفة Reziouq, Sherifah (جامعة وهران 1 أحمد بن بلة - مخبر الاتصال الجماهيري وسيميولوجية الأنظمة البصرية IAMGE, 2018)
The media have a great ability to convince public opinion and the constitution of their knowledge and impressions, and formation of mental and stereotype images, and perhaps the most controversial image is the image of Islam and Muslims in the Western media, the latter has been described Muslims as terrorism and intolerance, in America the image of Islam has troped in the eyes of the Americans from the stereotype drafted by Hollywood during the twentieth century to the current image of the most terrible compose by American media, with the increasing acts of violence, and what is produced by the media during the US presidential election campaigns and produced negative political speech for some candidates. So we browse in this intervention the nature of the stereotype image in the American media about Islam and Muslims, and the most important reasons that led this image for the Americans and the growing fear of Muslims to a higher level than it was after the 11 September 2001 attacks, and the role of American political speech during the last presidential election campaigns in embed this photo, and the Arab and Islamic efforts in correcting the image of Islam and Muslims.
تملك وسائل الإعلام قدرة كبيرة على إقناع الرأي العام وتكوين معارفه وانطباعاته، وتشكيل الصور الذهنية والنمطية، ولعل أكثرها جدلا هي صورة الإسلام والمسلمين المتداولة في وسائل الإعلام الغربية التي دأبت على وصف المسلمين بالإرهاب والتعصب، ففي أمريكا تراجعت صورة الإسلام في أعين الأميركيين من صورة نمطية مرجعية صاغتها هوليود خلال القرن العشرين إلى صورة أكثر بشاعة ينسجها الإعلام الأمريكي، وذلك مع تزايد أعمال العنف، وما تنتجه وسائل الإعلام خلال موسم حملة الانتخابات الرئاسية الأمريكية وما أنتجه الخطاب السياسي السلب لبعض مرشحيه. لذا نستعرض في مداخلتنا طبيعة الصورة النمطية المتداولة في الإعلام الأمريكي عن الإسلام والمسلمين، وأهم الأسباب التي أدت إلى تكون هذه الصورة لدى الأمريكيين وتنامي الخوف من المسلمين إلى مستوى أعلى مما كان عليه عقب هجمات سبتمبر 2001.
Keywords: وسائل الإعلام -- الإعلام الغربي -- الثقافة الغربية -- الولايات المتحدة الأمريكية -- الإسلام -- المسلمين -- الأنماط السلوكية -- الإعلام الأمريكي -- الخطاب السياسي -- الإسلاموفوبيا -- الصورة النمطية -- مستخلصات الأبحاث